2021
DOI: 10.1111/1468-0009.12547
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Framing of Immigration Policy in US Newspapers

Abstract: r Although immigration policy is recognized as a social determinant of health, less is known about how mechanisms, such as news coverage of policy, influence intermediary and proximal health processes like seeking health care.r The extent of news coverage of federal, state, and local exclusionary or integration immigration policies can influence public agendas regarding immigrant inclusion and exclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…airplane flights). As components of racialization processes, the immigration and immigrant policies described above not only contribute to constrained access to health-promoting resources, they also stigmatize Latiné and immigrant identities invoked in immigration and immigrant policy discourse and practice [ 43 , 45 ]– [ 48 ]. Racially minoritized individuals and communities find ways to leverage their power and agency to respond to and navigate racialization processes [ 43 , 49 , 50 ].…”
Section: Health Implications Of Immigration and Immigrant Policiesmentioning
confidence: 99%
“…airplane flights). As components of racialization processes, the immigration and immigrant policies described above not only contribute to constrained access to health-promoting resources, they also stigmatize Latiné and immigrant identities invoked in immigration and immigrant policy discourse and practice [ 43 , 45 ]– [ 48 ]. Racially minoritized individuals and communities find ways to leverage their power and agency to respond to and navigate racialization processes [ 43 , 49 , 50 ].…”
Section: Health Implications Of Immigration and Immigrant Policiesmentioning
confidence: 99%
“…At the heart of anti‐immigrant sentiments that uphold exclusionary immigration and immigrant policies is an underlying acceptance of immigrant criminalization, which casts some immigrants as “deserving” and others as “undeserving.” 66,67 This ideology overlooks the criminalization of people of color overall, justifies exclusionary immigration policies that link local policing with immigration enforcement, and disadvantages Black and Latino immigrants and other immigrants of color 68 . Additionally, this ideology diverts attention away from immigration as a human rights issue and the need for inclusive policies, 69–71 instead situating the topic as highly divisive and political. While overall national patterns indicate a general consistency or slight decline in the US population's concerns about immigration, 72 there has also been a trend toward increasingly extremist anti‐immigrant ideologies and organized anti‐immigrant movements 73,74 .…”
Section: Past Gains Successes Failures and Continuing Problems To Pro...mentioning
confidence: 99%
“…Research has demonstrated the significant impact framing effects can have on public opinion, as many form their opinions based on cues from media and political elites (Abrajano, and Singh 2009; Boomgaarden, and Vliegenthart 2007; Cargile, Merolla, and Pantoja 2014; Scheufele 2000; Scheufele, and Tewksbury 2006; Gil de Zuniga, Correa, and Valenzuela 2012; Iyengar, and Kinder 2010; Lecheler et al 2015; Valentino, Brader, and Jardina 2013; Zaller 1992). While there is a voluminous literature on the framing of immigration in media generally, there have been far fewer studies to-date examining how national and local media framing of immigration varies (De Trinidad Young 2022; Fryberg et al 2012; Kim et al 2011; Kim, and Wanta 2018; Lawlor 2015; Viladrich 2019). In the context of covid-19, there are reasons to believe local and national coverage will differ, especially in border states with large Latinx populations where the impact of covid-19 on these communities is likely to be more salient to readers.…”
Section: Immigration and Threat Narrativesmentioning
confidence: 99%